Little misery and other stories - Colahan, Marianne, author; Schwartz, Steven, advisor; Becker, Leslee, committee member; Kutcher, Lisa, committee member (colorado State University. Libraries, 2011)
This collection of work, composed over a period of three years, is a series of linked stories, meaning that the stories are connected to each other. One of the most important linking elements of these stories is family. The stories follow the protagonist, Beth, through various stages of her life, beginning when she is thirteen and ending when she is thirty. In addition to the stories told in Beth's POV, there are also two stories in the perspective of Abbie, Beth's younger sister. Beyond the linkage of character, these stories are about growth, loss, recovery, hope, and the impenetrable bond of family.